EFL learners’ perspective on English Honorifics (EHs) in Indonesia - Rina Herlina; Wawan Tarwana (Journal of Advanced Multidisciplinary Research, 2020)
Indonesian EFL learners (IELs) have been familiar with the practice of English Honorifics/EHs (Mr, Mrs, Miss, Sir and Ma’am) for decades. Mr, Mrs, Miss are followed by family name as the clan identity and Sir and Ma’am are for respectful address for adult man and woman. However, in Indonesia, it’s been the phenomenon because there seem to be a collision between how EFL learners practice EHs with what EHs are supposed to be used in English culture. The purpose of this study is to clarify and verify how Indonesian EFL learners perceive on EHs that have been interpreted and practiced for decades in Indonesia. This study applies double approaches. First, cross cultural study which employs content analysis by means of analyzing how EHs are interpreted and practiced under the setting of Indonesian culture. The sources to be analyzed are obtained from English handouts, chats and texts in social media among EFL students, as well as script deriving from teacher-EFL students’ classroom interaction. Second, case study which employs triangulation technique to examine some aforementioned sources. The result reveals that Indonesian EFL learners perceive that the practice of EHs (Mr, Mrs, Miss, Sir, Ma’am) have no difference with the ones applied in Indonesian culture. It means that there is no more difference in function between Mrs and Miss, Ma’am, Mr and Sir. Those have been considered the same in practice with Indonesian Honorifics (IHs) like ibu (Ma’am), bapak (Mr), nyonya (Mrs), dan nona (Miss) even though they have different function.  These have been conducted beyond EFL learners’ culture awareness of how native speaker of English uses EHs because there is an assumption that learning English doesn’t include learning its culture. For most Indonesian EFL learners, learning English as a foreign language is a matter of learning basic skills and linguistic features. So, if there are any further cultural encounters during learning English, they will be switched automatically to Indonesian culture. This study recommends English teachers to keep teaching English culture during teaching English in order to avoid learners’ misunderstanding in communication with English speaking people.